Evaluasi Implementasi Peraturan Daerah Nomor 7 Tahun 2016 Tentang Pengelolaan Sampah Di Kecamatan Panca Rijang Kabupaten Sidenreng Rappang - Sahrani, Aisyah; Rohady Ramadhan, Muhammad; Dema, Herman (STISIPOL Raja Haji, 2025)
The issue of waste management in Panca Rijang District, Sidenreng Rappang Regency, is the main focus of this study, considering the high volume of poorly managed waste and its negative impact on public health and the environment. This study aims to evaluate the waste management policy, which is expected to address these issues. The research method used is descriptive qualitative with purposive sampling, involving informants from the local government, UPT Waste Management employees, and the local community. Data were collected through observations, interviews, and documentation, and analyzed using NVivo 12 software. The results of the study show that the waste management policy in Panca Rijang District has had a positive impact on raising public awareness about the importance of waste management. However, its implementation still faces several challenges that hinder the effectiveness of the policy, such as limited facilities, low public participation, and insufficient supervision. The policy evaluation based on indicators of effectiveness, efficiency, adequacy, equity, responsiveness, and accuracy reveals that while the policy is fairly effective, there are still disparities in service, especially in remote areas, and inadequate facilities. The main obstacles identified in this study are the lack of waste management facilities, low public awareness, and limited funding for better management. This study provides valuable contributions to the local government in improving waste management, focusing on enhancing facilities, inter-agency coordination, and public education to support the sustainability of more effective, efficient, and equitable waste management policies in the future.